Structure, optical spectroscopy and dispersion parameters of ZnGa2Se4 thin films at different annealing temperatures - Fadel, M.; Yahia, I. S.; Sakr, G. B.; Yakuphanoğlu, Fahrettin; Shenouda, S. S. (Elsevier, 2012)
Thin films of ZnGa2Se4 were deposited by thermal evaporation method of pre-synthesized ingot material onto highly cleaned microscopic glass substrates. The chemical composition of the investigated compound thin film form was determined by means of energy-dispersive X-ray spectroscopy. X-ray diffraction XRD analysis revealed that the powder compound is polycrystalline and the as-deposited and the annealed films at T-a = 623 and 673 K have amorphous phase, while that annealed at T-a = 700 K is polycrystalline with a single phase of a defective chalcopyrite structure similar to that of the synthesized material. The unit-cell lattice parameters were determined and compared with the reported data. Also, the crystallite size L, the dislocation density delta and the main internal strain epsilon were calculated. Analyses of the AFM images confirm the nanostructure of the prepared annealed film at 700 K. The refractive index n and the film thickness d were determined from optical transmittance data using Swanepoel's method. It was found that the refractive index dispersion data obeys the single oscillator model from which the dispersion parameters were determined. The electric susceptibility of free carriers and the carrier concentration to the effective mass ratio were determined according to the model of Spitzer and Fan. The analysis of the optical absorption revealed both the indirect and direct energy gaps. The indirect optical gaps are presented in the amorphous films (as-deposited, annealed at 623 and 673 K), while the direct energy gap characterized the polycrystalline film at 700 K. Graphical representations of epsilon(1), epsilon(2), tan delta, - lm[1/epsilon*] and - lm[(1/epsilon* + 1)] are also presented. ZnGa2Se4 is a good candidate for optoelectronic and solar cell devices. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Defect chalcopyrite; ZnGa2Se4; Optical constants; Optical dispersion parameters; Effect of annealing